2020
DOI: 10.1080/0886022x.2020.1735417
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and acid-base disorders in cancer patients and its impact on clinical outcomes: evidence from a real-world study in China

Abstract: Background: This study aims to delineate the incidence of electrolyte and acid-base disorders (EAD) in cancer patients, to figure out the risk factors of EAD, then to assess the impact of EAD on patients' in-hospital clinical outcomes. Methods: Patients with the diagnosis of malignancies hospitalized during 1 October 2014 and 30 September 2015 were recruited in Zhongshan Hospital, Fudan University in Shanghai of China. Demographic characteristics, comorbidities, and clinical data, including survival, length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
2
31
0
3
Order By: Relevance
“…In this cohort of GBM patients, arterial hypertension, diabetes, a higher age, and a poor preoperative clinical status characterized the cohort of patients with hypochloremia. This observation is in line with previous studies, that also reported renal dysfunction, hypertension, and diabetes as risk factors for electrolyte disorders (8).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In this cohort of GBM patients, arterial hypertension, diabetes, a higher age, and a poor preoperative clinical status characterized the cohort of patients with hypochloremia. This observation is in line with previous studies, that also reported renal dysfunction, hypertension, and diabetes as risk factors for electrolyte disorders (8).…”
Section: Discussionsupporting
confidence: 94%
“…In cancer patients, electrolyte and acid-base disorders are reported in more than 50% (8). Moreover, kidney function and electrolyte homeostasis have been linked to patients' prognosis for several types of cancer (8,10,11). This study identi ed hypochloremia in GBM as an independent prognostic marker for 1-YS and OS, whereas all other investigated electrolytes and parameters of kidney function failed to display a consistent relation to patients' outcome.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations